Varför Paris men inte Prag?: Om namn i SAOL 14 - Sköldberg, Emma; Wenner, Lena (Nordisk tidskrift för socioonomastik, 2024)
The article reports on a study of the treatment of names in the latest edition of The Swedish Academy Glossary (SAOL 14). Initially, we present the principles for inclusion of names in Swedish monolingual dictionaries in general. After that, we discuss the names included in SAOL 14, on the basis of names listed in previous editions, dictionary user emails regarding the names, and the results of a web questionnaire on the topic. Finally, we address the question how the editors could handle this subset of headwords in the next edition of the glossary. This article reports on a study of the inclusion of names in the latest edition of The Swedish Academy Glossary (SAOL 14). We begin by presenting the principles for including names in Swedish monolingual dictionaries in general. We then discuss the names included in SAOL 14, based on those from previous editions, emails from dictionary users regarding the names, and the results of an online survey on the topic. Finally, we address the question of how the editors could approach this subset of headwords in the next edition of the glossary.